Models of civil servants’ digital competence: approaches to formation and evaluation - N. S. Gegedyush; E. V. Maslennikova; V. A. Osipov (Вестник университета)
The purpose of the study is to analyze the Russian practice of assessing the digital competence of civil servants and substantiate proposals for improving approaches to assessing and developing the competencies under study. The article presents an analysis of the existing requirements for the competence of Russian civil servants, officially fixed and the compliance of such requirements with the current and promising areas of activity of state bodies and the development of modern society in the context of digital transformation. The authors studied approaches to the formation and application of civil servants’ digital competence models, including on the basis of the job regulations content analysis. In the course of the study, the authors conclude that there is sufficient uniformity of approaches in the executive authorities regarding the content of qualification requirements, which is predetermined by the implementation of the methodological tools of the Ministry of Labor and Social Protection of the Russian Federation. But professional knowledge and skills in the field of information and communication technologies, in fact, duplicate the basic qualification requirements and do not reflect the use of information and communication technologies specifics in various industries and the differentiation of employees’ functionality depending on categories and groups of positions. The authors substantiate proposals regarding the formation of a model of digital competence, namely, the need to take into account the division of requirements into basic and professional ones, the reflection of differentiation into categories and groups of civil service positions.